Financial performance analysis of kerala state financial enterprises LTD - Divya Sasi (College of co-operation, banking and management, 2007)
The study entitled “The financial performance evaluation of the Kerala State Financial Enterprises LTD” was conducted to assess the performance of KSFE in terms of growth of business and financial strength.